PECULIARITIES OF WORD ORDER IN RUSSIAN AND ENGLISH SENTENCES - Gulzada Otambetova (Journals Park Publishing, 2023)
In the article the analysis of the peculiarities of word order in a sentence is presented by the examples of the English and Russian languages with the purpose of revealing similarities and differences in synthetic and analytic languages.
Keywords: word order; word order functions; inversion; rheme; syntactic peculiarities.